2002
DOI: 10.1136/bjo.86.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mutation detection by the Transgenomic wave analyser DHPLC identifies MYOC mutations in patients with ocular hypertension and/or open angle glaucoma

Abstract: Aims: To rapidly screen Scottish patients with a family history of open angle glaucoma (OAG) or ocular hypertension (OHT) for mutations in the myocilin gene (MYOC) and develop a new rapid screening method for MYOC mutation detection. Methods: All three exons of the MYOC gene were amplified by PCR from genomic DNA and subjected to direct DNA sequencing. Mutation detection methodology was also developed based on denaturing high performance liquid chromatography (DHPLC). A recurrent mutation was investigated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Ion-pair reversed-phase dHPLC identifies mutations by detecting heteroduplex formation between mismatched nucleotides in PCR-amplified DNA (40). Using the WAVE Nucleic Acid Fragment Analysis System (Transgenomics, Inc., Omaha, NE), we analyzed selected regions of each candidate TSG for the presence of mutations (41,42). Amplicons encoding the following functional domains were selected for dHPLC analysis: the kinase domain of CKI⑀; the PDZ2 domain of hDlg; and the NH 2 -terminal region of the EDD HECT domain.…”
Section: Introductionmentioning
confidence: 99%
“…Ion-pair reversed-phase dHPLC identifies mutations by detecting heteroduplex formation between mismatched nucleotides in PCR-amplified DNA (40). Using the WAVE Nucleic Acid Fragment Analysis System (Transgenomics, Inc., Omaha, NE), we analyzed selected regions of each candidate TSG for the presence of mutations (41,42). Amplicons encoding the following functional domains were selected for dHPLC analysis: the kinase domain of CKI⑀; the PDZ2 domain of hDlg; and the NH 2 -terminal region of the EDD HECT domain.…”
Section: Introductionmentioning
confidence: 99%
“…Information on MYOC variants in European POAG patients is presently limited (Cobb et al, 2002;Hulsman et al, 2002a;Michels-Rautenstrauss et al, 2002). In the present work, we investigated the genetic variation of the coding region of MYOC in 237 unrelated French POAG patients and 108 control subjects, using denaturing high performance liquid chromatography (DHPLC).…”
Section: Introductionmentioning
confidence: 99%
“…However, since all patients were recruited in a single centre, similar studies in other parts of the UK would be necessary to confirm that this is not a localized effect. A small study of affected sib-pairs in Scotland identified mutations in four families, of which three were Q368X (Cobb et al 2002). Likewise, we cannot exclude the possibility that our cohort differs clinically or demographically from those studied elsewhere.…”
Section: Discussionmentioning
confidence: 85%
“…All mutations were verified by analyzing a duplicate tube of stored blood. Exons 1 and 2 were analyzed by denaturing high performance liquid chromatography (dHPLC) using primers described by Cobb et al (2002). PCR was conducted essentially as described above, except that HotStar Taq polymerase and buffer (Qiagen) were used and the annealing temperature was 52°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation